PHYTOCHEMICAL SCREENING OF SAPTAPARNA (ALSTONIA SCHOLARIS R. Br.) BARK - Bhogayata, Kamlesh; Patel, B. R.; Chhaya, Bhakti; Doshi, *Krunal; Modha, Joban (AYUSHDHARA, 2015)
The Ayurvedic Pharmaceutical Industries use barks of many herbal drugs like Neema, Vata, Udumbara, Parisha, Saptaparna, Plaksha, Baboola etc. for the manufacturing of different herbal medicines. The stem bark of Alstonia scholaris R. Br. commonly known as Saptaparna in Ayurved, is in demand, due to its antipyretic, galactogogue, cardiotonic, anticancer, anti-helminthic etc. activities. But, the identification and separation of these barks drugs from each other is very difficult. Hence, a preliminary study has been done to ensure the basic phytochemical profile of A. scholaris R. Br. stem bark for identification of herbal drug. Physicochemical parameters, preliminary phytochemical screening, quantitative estimation of alkaloid and Thin Layer Chromatography (TLC) were carried out in the present study. Physicochemical data revealed, there is more amount of water soluble extractive value (27.10% w/w) than alcohol soluble extractive value (7.40% w/w). Facts of phytochemical screening showed presents of alkaloid, carbohydrate, tannin, saponin, flavanoids and cardiotonic glycosides in the sample. Result of TLC identification showed 7, 8, and 6 spots under short UV, long UV and after spray reagent respectively. The present study on phytochemical investigation of A. scholaris R. Br. bark will be helpful in developing standards for quality, purity and sample identification of this plant.